Impacts of environmental regulations on firm performance - Emerson, Oliver (2020)
Currently there are two dominant theories by professor Michael Porter explaining how firms could increase profitability by acting sustainably and what the potential outcome of complying with environmental regulations may be. The Porter hypothesis is about the impact of regulations and has further been developed into ‘creating shared value’ which explains how firms can reach new potential profitability by searching for sustainable business opportunities. Both of these theories are viewed separately and not in conjunction with one another even though one has motivated the other. Furthermore, the theories underlie a stakeholder theoretical approach, meaning that firms should focus on all various stakeholders in a firm, instead of a shareholder approach, which argues for firms to focus solely on profitability and shareholder value maximization. So far studies have been inconclusive regarding the validity of the theories and scholars find evidence both for and against.